Whey protein isolate modulates beta-carotene bioaccessibility depending on gastro-intestinal digestion conditions. (1st September 2019) - Iddir, Mohammed; Degerli, Celal; Dingeo, Giulia; Desmarchelier, Charles; Schleeh, Thomas; Borel, Patrick; Larondelle, Yvan; Bohn, Torsten
Highlights: Whey protein isolate modulates β-carotene bioaccessibility depending on digestive conditions. Reduced β-carotene bioaccessibility was pronounced with impaired lipid digestion. Strong positive influence of simulated peristalsis on β-carotene bioaccessibility. Abstract: Carotenoids are lipophilic phytochemicals; their intake has been associated with reduced chronic diseases. However, their absorption depends on emulsification during digestion and incorporation into mixed micelles, requiring digestive enzymes, gastric peristalsis, bile, and dietary lipids. In this study, we investigated whether whey-protein-isolate (WPI), a commonly consumed protein source, can modulate β-carotene bioaccessibility in vitro, especially under incomplete digestive conditions, i.e. under low digestive enzyme concentrations. Thus, amounts of pepsin, pancreatin, bile, co-digested lipids and kinetic energy and gastric digestion time were modified, and WPI at concentrations equivalent to 0/25/50% of the protein recommended dietary allowance (approx. 60 g/d) were added to β-carotene dissolved in oil. WPI enhanced bioaccessibility by up to 20% ( p < 0.001 ), especially under higher simulated peristalsis or reduced amount of dietary lipids. Conversely, they impaired bioaccessibility to one third ( p < 0.001 ) under incomplete digestive conditions. WPI modulated β-carotene bioaccessibility depending on digestive conditions.